In the shadow of the ancestors: the prehistoric foundations of the early Arabian civilization in Oman - Cleuziou, Serge; Tosi, Maurizio (Ministry of Heritage and Culture of the Sultanate of Oman, 2018)
This book, first published in 2007, offered the first and only summary of decades of archaeological research in the Oman Peninsula. The original eleven chapters are expanded and enhanced in this new edition by a number of new 'windows', written by a new generation of scholars, in order to include more recent research and interpretations.